Relação entre ansiedade e a convivência com animais de estimação em estudantes de medicina da Universidade Federal do Pará - STIVAL, Felipe Augusto de Cassia (2023)
Introduction: Anxiety is characterized by a vague feeling of fear and apprehension in which it derives from an anticipation of imminent danger, due to which the university environment would be a risk factor for such situations. One possibility to help with these anxious symptoms would be the degree of attachment to pets and could have positive outcomes in this portion of the population. Methodology: This was a case-control, cross-sectional, analytical and observational study. Held at the Federal University of Pará, with 206 students from the UFPA medical course, from the 1st to the 6th year. Data were collected in online questionnaires, addressing sociodemographic issues, the Lexington Attachmentto Pets Scale (LAPS), Trait-State Anxiety Inventory (IDATE), which distinguishes two subtypes: State- Anxiety and Trait-Anxiety. Data were analyzed using Biostats 5.0 software. Results: Most of the sample is composed of females (61.17%), single (92%), aged between 18 and 24 years (64%) and with an equivalent distribution between the years of the course. Most students have dogs as their main companion animal (79.2%). When analyzing Trait-Anxiety, it was found that 95.1% of the students had it, most of them having a moderate degree and State-Anxiety has a total of 94.66%. For Trait-Anxiety, gender (p=0.0001), degree of attachment (p=0.0311) and living or not with domestic animals (p=0.0186) was significant. No significance of State-Anxiety was observed with the variables. Conclusion: It was observed that the female audience has higher levels of Trait-Anxiety and that the degree of attachment is directly related to higher anxiety scores and that pets do not have lower levels of Trait-Anxiety. We conclude that not having pets has greater benefits for anxiety, however, it is still not possible to represent the causal relationship between these data, requiring further studies on this topic.